2018
DOI: 10.1002/andp.201800070
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Superconductors with Nonlinear Arcsin‐Electrodynamics

Abstract: Holographic s-wave superconductors with nonlinear arcsin-electrodynamics in the background of Schwarzschild anti-de Sitter black holes are investigated. The analytical Sturm-Liouville eigenvalue problem is explored and the scalar and electromagnetic fields are assumed not to influence the background metric (the probe limit). The critical temperatures of phase transitions depending on the parameter of the model are obtained. It is shown that in this case, the condensation formation becomes easier compared to Bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 70 publications
2
6
0
Order By: Relevance
“…In both cases, the transition temperature increases with the increase of charge density ρ. In particular, we have observed that in [39] for a given temperature as β increases the critical value of charge density increases similarly in the present model if we keep the temperature fixed at T = 0 and increase the analogous parameter Z 2 the critical value of charge density also increases. We have also studied the fermionic behaviour with the variation of the arcsin parameter Z 2 , where we find that with the increase of the arcsin parameter there is a transition from Fermi to non-Fermi regime.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In both cases, the transition temperature increases with the increase of charge density ρ. In particular, we have observed that in [39] for a given temperature as β increases the critical value of charge density increases similarly in the present model if we keep the temperature fixed at T = 0 and increase the analogous parameter Z 2 the critical value of charge density also increases. We have also studied the fermionic behaviour with the variation of the arcsin parameter Z 2 , where we find that with the increase of the arcsin parameter there is a transition from Fermi to non-Fermi regime.…”
Section: Discussionsupporting
confidence: 72%
“…In the present model as already mentioned in the introduction, we have considered a particular phase of the dual boundary theory. Comparing these results with the results of [39], we see that the boundary charge density ρ plays an important role in both the phases of the dual boundary theory. In the case of [39], ρ determines the critical phase transition temperature of the superconductor and also in the present case ρ determines the critical transition temperature from the regime of Fermi to Non-Fermi.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Gravitational fields are also treated as classical as quantum gravity is not developed yet. It was shown in [68] that in the model of holographic s-wave superconductors with arcsin-electrodynamics the condensation formation depends on the parameter β weakly as compared with the model with BI electrodynamics. In addition, to create the condensation is easier in arcsin-electrodynamics comparing to BI electrodynamics.…”
Section: Introductionmentioning
confidence: 99%